2015
DOI: 10.1002/2014jc010363
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the mesoscale variability and in extreme sea levels over two decades as observed by satellite altimetry

Abstract: A data set of precise radar altimeter sea surface heights obtained from the same 10 day repeat ground track has been analyzed to determine the magnitude of change in the ocean ''mesoscale'' variability over two decades. Trends in the standard deviation of sea surface height variability each year are found to be small (typically 0.5 percent/yr) throughout the global ocean. Trends in positive and negative extreme sea level in each region are in general found to be similar to those of mean sea level, with some sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…In the Caribbean, Torres and Tsimplis (2013) found that 2 out of the 5 sites they studied were anti-correlated with ENSO, but Menéndez and Woodworth (2010) found no significant relationship. Woodworth and Menéndez (2015) found that ESL largely followed the pattern of MSL response to ENSO. By contrast, the tropical west Pacific and the coast of Australia showed a negative correlation (Feng and Tsimplis, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…In the Caribbean, Torres and Tsimplis (2013) found that 2 out of the 5 sites they studied were anti-correlated with ENSO, but Menéndez and Woodworth (2010) found no significant relationship. Woodworth and Menéndez (2015) found that ESL largely followed the pattern of MSL response to ENSO. By contrast, the tropical west Pacific and the coast of Australia showed a negative correlation (Feng and Tsimplis, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Regional frequency analysis has occasionally been used with tide‐gauge data to estimate ESL probabilities while overcoming some of the spatial limitations inherent to the global tide gauge network (Hall et al, ), but to our knowledge more sophisticated spatiotemporal extreme value methods (e.g., Reich & Shaby, ) have not yet been employed in this context. Recent advances using satellite altimetry show promise in the ability to complement tide‐gauge observations by predicting coastal ESLs using offshore ESL observations combined with continental shelf characteristics (Lobeto et al, ; Woodworth & Menéndez, ).…”
Section: Projections Of Extreme Sea Level Change and Associated Floodingmentioning
confidence: 99%
“…In addition to long‐term trends, ESL probabilities exhibit seasonal and long‐tidal cycles and climate mode covariability (e.g., Aucan et al, ; Haigh et al, ; Marcos et al, ; Menéndez & Woodworth, ; Wahl & Chambers, ; Woodworth & Menéndez, ), which can enhance flooding when contributing processes align (Sweet et al, ; Thompson et al, ). Diagnosing contributory processes within statistical ESL models can provide a degree of predictability if the processes are deterministic in nature or predictable to some degree by climate models (Menendez et al, ; Menéndez & Woodworth, ; Sweet & Park, ; Sweet et al, ; Widlansky et al, ).…”
Section: Projections Of Extreme Sea Level Change and Associated Floodingmentioning
confidence: 99%
“…One of the most important challenge for coastal adaptation is the rise of sea-level caused by anthropogenic climate change (Slangen et al, 2014b;Dangendorf et al, 2015). At present, there are already evidences that extreme water levels are becoming higher and more frequent (Marcos et al, 2009;Menéndez and Woodworth, 2010;Woodworth et al, 2011;Woodworth and Menéndez, 2015). At longer timescales, contributions from polar ice-sheets largely exceeding one meter are now recognized possible (Golledge et al, 2015;Hansen et al, 2015;Winkelmann et al, 2015).…”
Section: Introductionmentioning
confidence: 99%